STATUS MIKROBIOLOGI (Total Plate Count dan Staphylococcus aureus) SUSU SAPI PERAH DI KABUPATEN TANGGAMUS PROVINSI LAMPUNG - Oktora Luhur Handika; Veronica Wanniatie; Purnama Edy Santosa; Arif Qisthon (Department of Animal Husbandry, Faculty of Agriculture, University of Lampung, 2020)
This study aimed to determine the microbiological status (Total Plate Count and Staphylococcus aureus) of milk of dairy cows of people's farms. Research location was in Tanggamus Regency, Lampung Province. This research used survey method with census methods. Fresh milk samples were taken during milking in the morning, which is as much as 250 ml from all lactating cows. In addition, this study also used questionnaire to know the condition of the dairy cows. Nineteen milk samples were analyzed at the Veterinary Public Health Laboratory of Lampung Veterinary Center, Bandar Lampung. Analysis of milk microbiological status was based on Total Plate Count and Staphylococcus aureus. The results of this study indicated that 100% of milk samples had Total Plate Count and Staphylococcus aureus values ​​below the maximum SNI number of 3141.1: 2011. Milk of dairy cow in Tanggamus Regency, Lampung Province is feasible and safe for consumption. Keywords: Dairy cows, Microbiological status, Milk.